PENGARUH INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMODERASI - Suardinatha, Made Hardy; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of job satisfaction strengthen auditor independence and professionalism to audit quality. This study was conducted in 7 KAP in Bali Province. Samples are taken as much as 81 auditors, the data collection methods used in this research is survey method with questionnaire technique. Data analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis found that job satisfaction does not affect the auditor's independence and professionalism to audit quality. This suggests that a good auditor is satisfied or not satisfied with the work still required to act independently and professionally for the independence is an absolute requirement that must be owned by an auditor to affect audit quality, and professionalism of auditors should be enhanced in order to affect the quality of the audit.
Keywords: Independence, Professionalism, Job Satisfaction, Audit Quality